Theoretical Analysis of Fiber Bragg Grating Tunable Filter Utilizing Tensile /Compression Technique - Ayad Z. Mohammed; A. K. Abass; Samar K. Ibrahim; Wail Yass Nassir (Diyala Journal of Engineering Sciences, 2018)
In this paper a wideband tunable filter based on fiber Bragg grating (TF-FBG) utilizing tensile/ compression technique is theoretically investigated. According to the results, a wide tuning range is achieved about 48.36 nm in Cband region from 1513.7 nm to 1562.1 nm; 12.09 nm for tension and 36.27 nm for compression (C-band refers to the wavelength range 1530–1565 nm). While, for L-band region the wavelength shift is slightly greater than in the C-band region about 49.272 nm from 1543 nm to 1592.3 nm; 12.3 nm for tension and 36.972 nm for compression (Lband refers to the wavelength range 1565 –1625 nm).